الدافع وراء الاستحواذ في أوجين أونيلز إيل - كمال الماس (مجلة الفتح للبحوث التربوية والنفسية, 2023)
Abstract This Study is an attempt to examine the motif of obsession in O'Neill's Ile (1917), a one-act play. This study also tries to explain in what way O'Neill's protagonist is an obsessed and haunted man. Eugene O'Neill started with short slice-of-life dramas dealing with the miseries, delusions and obsessions of men adrift in the world. In the summer of 1916 he became the undisputed master of the one act play form in America. The playlets In the Zone, The Long Voyage Home (1917) and The Moon of the Caribees (1918) along with O'Neill first Provincetown production made up the quartet of plays produced under the collective title S.S. Glencairn. Besides, number of independent pieces such as ILe (1917), The Rope (1918) and Where the Cross is Made (1918) enhanced the young author's reputation by the end of World War I.1 ILe is especially representative of his early naturalistic- symbolic style with its mordant treatment of a New England sea captain’s obsessive pride to hunt whales for their oil or ile as it is indicated in the play, which drives his lonely wife mad. This little play exemplifies O’Neill’s taste for tragic irony—his peculiar concern with dangerous "obsession that resembles the hubris of classic tragedy and his fascination with sea"2 as a mystery and seduction, and as a symbol of malignity.